Development of an Information System with an Herbal Database of East Java Suppliers and Distributors - Oeke Yunita; Melania Dwi Savitri; Hendra Dinata; Alfian Hendra Krisnawan (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
The production and marketing operations of small traditional medicine businesses (UKOT) in Indonesia heavily depend on the availability and choice of distributors of herbal products as well as suppliers of raw materials. The guarantee of accuracy and convenience of access to supplier and distributor data at UKOT PT X in Surabaya, East Java, can be supported by an internal information system that includes a database of East Java suppliers and distributors. Data was gathered via an interview with the Responsible Pharmacist (APJ) and documentation on PT X's records. Subsequently, the completed data generated from the chosen documentation is entered into the database that is a component of PT X's internal information system. The analysis was conducted on PT X's internal database, with an emphasis on its completeness, correctness, and accessibility. This result was obtained by 80% of data completeness evaluation ranges. All respondents properly answered questions about data about finished product suppliers and distributors from PT X's internal information system database. Ninety-three percent of respondents agree that the database in PT X's information system is very easy to access in terms of data display, language, and search feature functions.